Latex and rosin films as alternative waterproofing coatings for 3-layer sugarcane-bamboo-based particleboards. (May 2019) - Nakanishi, Erika Yukari; Cabral, Matheus Roberto; Fiorelli, Juliano; Christoforo, André Luís; Gonçalves, Paulo de Souza; Savastano Junior, Holmer
Abstract: This paper studied two alternative polymeric films based on natural latex and rosin as a waterproofing coating for 3-layer sugarcane-bamboo-based particleboards (3LP). To study the roughness as well as evaluate the coating surfaces on the 3LP, scanning confocal electron microscopy (SCEM) was used. The wettability performance of the coatings was evaluated by the surface energy through the contact angle method. The 3LP coated thermal, physical and mechanical properties were evaluated following ASTM-E1530: 2011 and ABNT NBR 14810 standards, respectively. Physical results indicated latex and rosin coatings significantly decreased water permeability in the 3LP showing swelling in thickness (TS) values of 1.72 and 2.43%, respectively, when compared 3LP without coating (3LP-Control) of 12.90%. The latex and rosin coatings on the 3LP did not influence the thermal properties. Mechanical properties of modulus of rupture (MOR)and modulus of elasticity (MOE) under bending solicitation shown that all 3LP met the ANSI Standard A208.1–1999 requirements. Latex successfully formed a smooth and continuous film which covered the surface pores of the 3LP, whereas rosin did not form a smooth and continuous, forming only a thin film on the 3LP. Highlights: Films based on latex and rosin as a waterproofing coating for 3LP Physical results indicated that the coatings decreased water permeability. 3LP coated with latex presented TS values of 1.72% after 24 h in water. 3LP coated with rosin presented TS values of 2.43% after 24 h in water. Latex formed a smooth and continuous film covering the surface of the 3LP